2013
DOI: 10.4049/jimmunol.1202924
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: IL-17–Secreting Innate Lymphoid Cells Are Essential for Host Defense against Fungal Infection

Abstract: Soil microbiome modification may alter system function, which may enhance processes like bioremediation. In this study, we filled microcosms with gamma-irradiated soil that was reinoculated with the initial soil or cultivated bacterial subsets obtained on regular media (REG-M) or media containing crude oil (CO-M). We allowed 8 weeks for microbiome stabilization, added crude oil and monoammonium phosphate, incubated the microcosms for another 6 weeks, and then measured the biodegradation of crude oil components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
321
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(348 citation statements)
references
References 45 publications
14
321
3
2
Order By: Relevance
“…34 IL-17-producing ILCs were also reported to determine protection against C. albicans in a murine model of oropharyngeal candidiasis. 33 Even neutrophils can be a source of IL-17, 35 and their importance in a model of keratitis by Aspergillus was also documented. 36 In conclusion, our findings add T.rubrum as another NLRP3 inflammasome activator, supporting this system as another component of the inflammatory process in dermatophytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 IL-17-producing ILCs were also reported to determine protection against C. albicans in a murine model of oropharyngeal candidiasis. 33 Even neutrophils can be a source of IL-17, 35 and their importance in a model of keratitis by Aspergillus was also documented. 36 In conclusion, our findings add T.rubrum as another NLRP3 inflammasome activator, supporting this system as another component of the inflammatory process in dermatophytosis.…”
Section: Discussionmentioning
confidence: 99%
“…One example is the innate-like lymphoid cells (ILCs), a recently identified lymphoid lineage population whose functions show innate immunity-like features, as a fast-response timing. 32,33 Kim et.al. showed that obesity-associated airway hyperactivity is driven by ILCs-derived IL-17 and the recruitment of these Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of T h 17 and T h 22 cells has been correlated with the breakdown of mucosal integrity, microbial translocation, and chronic immune activation (22,40,41). Because ILC3 cells play critical roles in formation of lymphoid tissue, adaptive immunity, regulation of mucosal microbiota via AhR, restoration of secondary lymphoid tissues after injury, and maintenance of intestinal memory CD4 T cells (3,17,18,45), their losses undoubtedly contribute to compromised mucosal immunity in HIV infection and AIDS, including failure of humoral immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…These ILC3 cells highly expressed CD90 (∼63%) and aryl hydrocarbon receptor and produced IL-17 (∼63%), IL-22 (∼36%), and TNF-a (∼72%) but did not coexpress CD4 or NK cell markers. The intestinal ILC3 cell loss correlated with the reduction of total CD4 + T cells and T helper (T h ) 17 and Th22 cells in the gut during SIV infection (P < 0.001). Notably, ILC3 could be induced to undergo apoptosis by microbial products through the TLR2 (lipoteichoic acid) and/or TLR4 (LPS) pathway.…”
mentioning
confidence: 97%
See 1 more Smart Citation